PERKEMBANGAN DAN LANDASAN TEORI KAJIAN ILMU BALAGHATUL QUR’AN - Afiqah Zahraa; Astri Wulandari (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
Balaghah is a branch of Arabic language studies that plays an important role in understanding the beauty and miraculous nature of the language of the Qur'an. This study aims to examine the development of balaghah and the theoretical foundations that form the basis of its study. The method used is qualitative research with a literature study approach through data collection from relevant books and journals. The results of the study show that balaghah science developed since the early days of Islam and was systematized through the thoughts of scholars such as ‘Abd al-Qahir al-Jurjani and al-Sakkaki. Theoretically, balaghah science consists of three main branches, namely ma'ani science, bayan science, and badi’ science, which play a role in explaining the beauty and depth of the meaning of the language of the Qur'an.